Attitudes Toward Sexual Violence Survivors: Differences Across Professional Sectors in Kenya and the Democratic Republic of the Congo. Issue 24 (December 2018) - Ferdowsian, Hope; Kelly, Scott; Burner, Mary; Anastario, Mike; Gohlke, Grace; Mishori, Ranit; McHale, Thomas; Naimer, Karen
Sexual violence survivors who decide to report their assault interact with health care, law enforcement, and legal and judicial professionals. Professionals' attitudes about sexual violence and survivors play an important role in caring for survivors and in the pursuit of justice. Despite evidence showing the relationship between service provider beliefs and survivor outcomes, relatively little is known about professionals' beliefs about sexual violence or their attitudes toward sexual violence survivors. Between June 2012 and December 2014, our study examined the beliefs and attitudes of 181 professionals from the health care, legal, and law enforcement sectors in the Eastern Democratic Republic of the Congo (DRC) and the Rift Valley region of Kenya, areas with a high prevalence of sexual violence. To determine correlates of beliefs and attitudes about sexual violence and sexual violence survivors, multiple logistic regression models were adjusted for demographic and occupational characteristics. Respondents who agreed that survivors got what they deserved (7%) or that survivors should feel ashamed (9%) were the minority, while those who would be willing to care for a family member with a history of sexual violence (94%) were the majority. Profession was significantly associated with beliefs and attitudes about sexual violence and survivors. Law enforcement professionals were more likely than health professionals and lawyers to indicate that survivors should feel ashamed. Our findings suggest a need for interventions that adequately address potentially harmful beliefs and attitudes of some professionals serving sexual violence survivors.